Przed bramą. Od alegorii do katachrezy - Kunz, Tomasz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The allegorical story entitled At the Gate, which appeared as the eighth chapter of Elizabeth Costello, a novel by John M. Coetzee, ostentatiously alludes to the famous parable by Franz Kafka, Before the Law. Deconstructing an allegory with its own devices, Coetzee points to the need to replace allegorical reading, transform vague narrative meanings into unambiguous ideological senses, with interpretation, which always has to negotiate between the rule of the Law and the idiomatic singular voice, since both of them — the Law, as well as the narrative — are equally necessary to make interpretation possible. Rhetorically, it means replacing a readable allegory with a catachresis, which, by its ambiguous and intermediate status, eludes the opposition of the original and the figurative, situating itself into the borderland between them. Thus, it is a catachresis which becomes a figure of literature, which cannot make unambiguous ideological choices, but at the same time it cannot avoid them, if it is to hold any existential value.